A just organized youth sport. Issue 1 (2nd January 2023) - Torres, Cesar R.; López Frías, Francisco Javier
ABSTRACT: Organized youth sport has become a prominent activity in Western societies, one around which myriad families structure their daily lives. Despite its popularity, or rather because of it, youth sport is besotted with complex problems. One distinctive set of problems pertains to children's opportunities to benefit from engagement in sport. Such problems require a reflection on the conditions of justice. The goal of this paper is to explore ethical guidelines to make youth sport more just. The paper begins by characterizing childhood, youth, and youth sport. Then, it articulates considerations of justice in youth sport. Together, these sections provide a basis to formulate the general features of a just youth sport. What emerges is a vision of youth sport that the adults involved in it should emphasize and implement if their young charges, and youth sport, are to flourish, as well as a novel approach to formulating and justifying normative criteria to make youth sport more just.